Rekonstruksi Nilai Keadilan dalam Ekonomi Islam Perspektif Muhammad Baqir Al-Sadr Berbasis Maqashid Syariah dan Implementasinya dalam Praktik Ekonomi Syariah Kontemporer - Adi Mansah; Titien Yusnifa; Aldi Surizkika (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2026)
This study aims to analyze the reconstruction of the concept of Islamic economic justice according to Muhammad Baqir Al-Sadr, utilizing the Maqashid Sharīah (objectives of Sharia) approach, and to examine its relevance to contemporary Sharia economic practices. Al-Sadr’s thought positions distributive justice as the core of the Islamic economic system, distinguishing it from both capitalism and socialism. The study employs a qualitative approach via library research, analyzing Al-Sadr’s seminal work particularly Iqtisaduna alongside literature on Maqashid Shari'ah and contemporary Islamic economics. Content analysis and conceptual analysis serve as the analytical methods. The findings indicate that Al-Sadr’s reconstruction of justice values ​​can be reinforced through the Maqashid Sharīah paradigm, specifically regarding the preservation of wealth (Hifz Al-Mal), the preservation of life (Hifz Al-Nafs), and the public interest (Maslahah Al Ammah). Implementation is reflected in the strengthening of wealth distribution systems, the development of Islamic social finance (such as zakat, waqf, and infaq), the application of profit-and-loss sharing, equitable governance of Sharia financial institutions, and Sharia-compliant digital economic regulations. The study concludes that integrating Muhammad Baqir Al-Sadr’s thought with Maqashid Shari'ah yields an Islamic economic paradigm that is more adaptable to modern economic challenges without compromising the principle of substantive justice.